2004
DOI: 10.1074/jbc.m402034200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α, Interleukin-1β, and Interferon-γ Stimulate γ-Secretase-mediated Cleavage of Amyloid Precursor Protein through a JNK-dependent MAPK Pathway

Abstract: The deposition of the amyloid beta (Abeta) peptide in neuritic plaques plays a critical role in the pathogenesis of Alzheimer's disease (AD). Abeta is generated through the proteolysis of amyloid precursor protein (APP) by the sequential actions of beta- and gamma-secretases. Although recent evidence has unveiled much about the biochemical identity and characteristics of gamma-secretase, the mechanism regulating endogenous gamma-secretase activity remains elusive. To identify possible extracellular signals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
256
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(283 citation statements)
references
References 52 publications
17
256
1
2
Order By: Relevance
“…4A), similar to that specific for APP-C99 (35). T-Rex HeLa cells constitutively expressing the tetracycline repressor protein (tetR) were co-transfected with pGL4.31, a plasmid encoding a Gal4-driven luciferase reporter gene and either with a plasmid encoding a tetracyclinedriven FL-NRXN3␤ fused to the Gal4 DNA binding domain and to the VP16 activation domain (NRXN3␤-GV) or encoding the C-terminal APP fragment fused to Gal4-VP16 (APP-C99-GV).…”
Section: Nrxn3␤ Is Sequentiallymentioning
confidence: 99%
See 1 more Smart Citation
“…4A), similar to that specific for APP-C99 (35). T-Rex HeLa cells constitutively expressing the tetracycline repressor protein (tetR) were co-transfected with pGL4.31, a plasmid encoding a Gal4-driven luciferase reporter gene and either with a plasmid encoding a tetracyclinedriven FL-NRXN3␤ fused to the Gal4 DNA binding domain and to the VP16 activation domain (NRXN3␤-GV) or encoding the C-terminal APP fragment fused to Gal4-VP16 (APP-C99-GV).…”
Section: Nrxn3␤ Is Sequentiallymentioning
confidence: 99%
“…The NRXN3␤-GV-encoding sequence was then inserted into the pcDNA transmembrane 5/TO vector (Invitrogen), and its expression was placed under the control of two tetracycline operator sequences (TO). The APP-C99-GV construct was a gift from M. Wolfe (35). The luciferase reporter vector pLG4.31 (Promega) contains the synthetic firefly luciferase gene (luc 2) placed under the control of the GAL4UAS response element.…”
Section: Methodsmentioning
confidence: 99%
“…Our data also fit with recent findings showing that the phenotype of accumulating microglia changes as AD-like pathology progresses in tgAPP-PS1 mice (Hickman et al, 2008), from a protective, A␤-clearing role during early phases to an enhanced production in inflammatory cytokine and loss in A␤-clearing capabilities during later disease phases. Furthermore, it is conceivable that, in addition to dysfunctional Reelin signaling, proinflammatory cytokines including interferon-␥, TNF-␣ (tumor necrosis factor-␣), and interleukin-1, shown to be secreted from glia (Hickman et al, 2008) and demonstrated to be involved in ␤-secretase upregulation (Yamamoto et al, 2007) and ␥-secretase-mediated APP cleavage (Liao et al, 2004), contribute to A␤ production and accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rac1, as well as other small G proteins, has been implicated in the pathways triggered by inflammatory mediators, such as interleukin (IL)-1␤, IL-6, or tumor necrosis factor-␣, and by growth factors, such as transforming growth factor-␤ or platelet-derived growth factor, that have been found to be up-regulated in AD brains (24,25). These signaling pathways have been shown to stimulate the generation of A␤ (26). The involvement of Rac1 in AD is further stressed by the observation that an up-regulation of neuronal Cdc42/Rac1 occurs in selected neuronal populations of the AD brain in comparison with age-matched controls (27).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%